BUKU DIGITAL INTERAKTIF SISTEM AIR CONDITIONING (AC): UPAYA MEMBELAJARKAN SISWA PADA MASA PANDEMI COVID-19 DI DAERAH YANG MISKIN SINYAL SELULER. - Indrawan Fardiansah; Yayat Ruhiyat; Suherman Suherman (JURNAL PENDIDIKAN TEKNIK MESIN, 2021)
Indonesia in the 2019 PISA report for reading scores has fallen far from the previous, which is ranked 72 out of 79 countries (Hewi & Shaleh, 2020). One of the external factors that influence is the learning process. Interactive Digital Book (BUDIN) is an alternative media that can be used to increase students' reading interest (Rosyadi & Santosa, 2019). The research objective was to determine the increase in the reading intensity of students through the BUDIN air conditioning system as well as an alternative learning process during the Covid-19 pandemic that could be used in areas with poor cellular signal. The method in this research is using survey explanatory method. Data analysis was carried out by descriptive analysis (A. Muhidin and Maman A, 2007: 53). BUDIN air conditioning system is intended for students in class XI automotive engineering expertise program.From the research results, it was found that independent learning using BUDIN increased reading intensity from before. It can be seen that after using BUDIN, the reading intensity has increased. The reading intensity of the very high category rose to 16%, then the high category increased to 47%. While the reading intensity of the moderate category decreased to 25% of students, as well as students in the low category, it decreased to 12% of students from the previous 38% of students.